Strategi Strategi Branding Untuk Meningkatkan Omzet Penjualan Usaha Mikro Kecil Menengah (UMKM) - Widayanti, Rahayu (TERANG, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Tumpang District, Malang Regency, which produce food under the JAWA and Alchikmah brands, do not yet have a branding strategy to differentiate the company's products from competitors, so they experience difficulties in marketing. This activity aims to increase MSME knowledge about the importance of branding to increase sales turnover. The output targets of this activity are 1) providing knowledge about good packaging design, 2) knowledge of good logo and brand design, 3) knowledge of branding strategies to increase sales turnover, 4) knowledge of photography techniques on food products, 5) knowledge about videography techniques on food products, 6) knowledge of marketing strategies using social media. The methods used in the workshop activities include lectures, discussions and questions and answers, as well as simulations. The stages carried out in this activity are 1) field observations 2) training and workshops, 3) evaluation and mentoring. The conclusion from the results of this workshop is that the level of MSME understanding of the entire program is 92%. Some things that need to be considered are the need to carry out ongoing training to optimize knowledge about branding strategies to increase sales turnover, about photography and videography techniques for food products, and increasing marketing through social media.